Incidence of symptomatic brain metastasis following radical radiotherapy for non-small cell lung cancer: is there a role for prophylactic cranial irradiation? - Khan, E; Ismail, S; Muirhead, R (2012)
OBJECTIVE: Brain metastases following radical radiotherapy for non-small cell lung cancer (NSCLC) are a recognised phenomenon; however, the incidence of symptomatic brain metastasis is currently unknown. The aim of the study was to identify the number of patients, staged in accordance with National Institute for Health and Clinical Excellence (NICE) guidance, who developed symptomatic brain metastasis following radical radiotherapy. There are two aims: to evaluate NICE guidance; and to provide vital information on the likely benefit of prophylactic cranial irradiation (PCI) in reducing neurological symptoms from brain metastasis. METHODS: A retrospective review of 455 patients with NSCLC who had undergone radical radiotherapy in 2009 and 2010 was performed. Computer-based systems were used to identify patient and tumour demographics, the staging procedures performed and whether brain imaging had identified brain metastasis in the follow-up period. RESULTS: The total number of patients with brain metastasis within 6 months was 3.7%. The proportion of brain metastasis within 6 months in Stage I, II and III NSCLC throughout both years was 2.8%, 1.0% and 5.7%, respectively. Within the follow-up period (median 16 months, range 6-30 months), the total number of patients who developed symptomatic brain metastasis was 7.9%. CONCLUSION: Patients staged in accordance with NICE guidance, of whom only 7.7% underwent brain staging, have a minimal incidence of brain metastasis following radical radiotherapy. The number of patients developing symptoms from brain metastasis following radical radiotherapy may be less than the morbidity caused by PCI. ADVANCES IN KNOWLEDGE: This finding supports the NICE guidance and brings into question the potential benefit of PCI.